Study of gas-liquid flow in microchannels - Tan, Siang Fu. (2009)
The main purpose of this project is to investigate the effect of aspect ratio on gas-liquid flow characteristic in micro scale system. Hence, the microchannel with different aspect ratio would be created and mixing efficiency in respective channel would be studied. To study the mixing efficiency, the formation of bubble must be regular and steady so that the results are reliable. As a result, the author also investigated the bubble formation process. The geometry of the designed microchannel is a combination of T-junction and meandering channel which are proved efficient in bubble formation and in enhancing mixing. The channel depth and channel width are the factors of aspect ratio and the designated depth is always larger than the channel width. This design is different with the common microchannel design which channel width larger than channel depth. The microchannel was fabricated by polymethylmethacrylate (PMMA) which commonly used in fabrication of microchannel. This is due to its cheap cost, chemically inert, optically transparent and hydrophilic feature. The PMMA chips were cut out by using laser machining. The power setting and the beam speed of laser machine must be taken care as it affects the dimensions of channel and surface roughness. Subsequently, the cut out PMMA chips were heat bonded to form the microchannels. The two immiscible liquids used in the experiment were distilled water (DI water) and fluorescence. They were initially pumped from two inlets by syringe pump and flow into the microchannel as main flow and the air was dispersed into the liquids flow at the T-junction. Thus, the author compared the mixing degree between system with bubble and without bubble. The effect of aspect ratio on mixing efficiency was investigated by varied the liquid flow rate and observed the degree of mixing at specific location in microchannel. Finally, the investigation on the effect of the aspect ratio and bubble formation would be presented and future work would be discussed at the end of the report.